The Allen Site : a Paleoindian camp in southwestern Nebraska - Bamforth, Douglas B. (Book collections on Project MUSE., 2007)
Recent research on the intriguing Allen Site in southwestern Nebraska and the nearby Medicine Creek sites has revealed a wealth of new information on the land and animal use of the early inhabitants.